Islamic behavioral treatment game for ADHD kids (AdabI) - Nor Syafiqah Izazi, Jamil (2019)
Attention deficit hyperactivity disorder (ADHD) is a medical condition in which the person who have this kind of disease is unable to control their impulses and hyperactive. ADHD kids have three types of ADHD which are inattentive, hyperactive and impulsive. ADHD disease can be treat base on treatment that only focusing on changing behaviors. The most common problem is there are no specific game for ADHD kids with Islamic contents. Furthermore, the other problem is the contains of the existing games are not suitable with ADHD kids and there are no ADHD games that created specifically in Malay language. So, this game will educate them some Islamic moral values that they can practice and learn in their daily live and at the same time helping them in handling their behaviors as the game will grab their attentions. The goal of this project is to create a 2–Dimensional Islamic behavioral treatment game for ADHD kids where for controlling the behaviors and manners. To achieve this goal, the ADHD kid’s behaviors and related game applications were study, designing and develop the mobile 2–Dimensional Islamic treatment behavioral game for ADHD kids and evaluate the effectiveness of AdabI game towards ADHD kids. The target ADHD kids are in range of age from 5 until 12 years old. The other target user are teachers and parents. This game will be developed by Unity application software and in Bahasa Malaysia. In this project, Rapid Application Development (RAD) is a suitable methodology to be used as it increases the speed of project development and its quality. There are five phases in the RAD model which are requirements planning, user design, construction, testing and cutover. After a test was done by two of ADHD kids, the results are the game is functions well and the ADHD kids can concentrate and give attention to the game. They can play and follow the instructions well and this make them to be able to seat still. For conclusion, this game helps to treat ADHD behaviors and educate them Islamic manners and values.